Influencing the environmental factors on the abundance of puerulus Panulirus homarus in the Mentawai Islands, West Sumatra, Indonesia (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Suparno, Yusra, Lubis AS, Viza AFY. 2024. Influencing the environmental factors on the abundance of puerulus Panulirus homarus in the Mentawai Islands, West Sumatra, Indonesia. Biodiversitas 25: 3758-3767. The lobster puerulus, the final larval stage of the spiny lobster, is significantly influenced by environmental factors, making it crucial for sustainable aquaculture development. This study aimed to analyze how these factors affect the abundance of puerulus Panulirus homarus (Linnaeus, 1758) in the Mentawai Islands, West Sumatra, Indonesia has practical implications for aquaculture. A one-way analysis of variance revealed that the temporal period significantly impacts the abundance of puerulus P. homarus (P
Keywords: Abundance, environmental factors, Mentawai Islands, puerulus